Management of Public Transportation in Order to Conduct Operational Terminal (Case Study in Mojosari Terminal, Mojokerto Regency) - Setia, Prayudha (Jurnal Administrasi Publik, 2013)
Abstract: Management of Public Transportation in order to Conduct Operational Terminal (Case Study in Mojosari Terminal, Mojokerto Regency). Public transportation has an important role in supporting human activity because the existence of public transportation can be able to give significantly advantage for all society level. In the public transportation activity needs to be supported an availability of transportation needs, they are consist of: means of transportation and transportation infrastructure in this case include terminal as the place for transportation service which has function to discharge and also departure passenger (Nasution, 2004: p. 15). Thus, the existence of management of public transportation in order to conduct operational terminal will be able to determine the level of terminal function fulfillment. This research purposes to break down and analyze about management of public transportation in order to conduct operational terminal, especially in Mojosari Terminal Mojokerto Regency that has been categorized relative new and managed directly by Department of Transportation Communication and Informatics (Dinas Perhubungan Komunikasi dan Informatika or Dishubkominfo) Mojokerto Regency. Keywords: Management of Public Transportation, Operational Terminal. Â  Abstrak: Manajemen Transportasi Publik dalam rangka Menyelenggarakan Operasional Terminal (Studi Kasus di Terminal Mojosari, Kabupaten Mojokerto). Transportasi publik memiliki sebuah peran penting di dalam menunjang kegiatan manusia, karena kehadiran transportasi publik mampu memberikan manfaaat yang signifikan bagi semua lapisan masyarakat. Di dalam kegiatan transportasi publik perlu ditunjang ketersediaan kebutuhan transportasi, yaitu: sarana angkutan dan prasarana angkutan dalam hal ini termasuk terminal sebagai tempat pelayanan angkutan yang berfungsi sebagai pemberhentian dan pemberangkatan penumpang (Nasution, 2004: hal. 15). Oleh karena itu, adanya manajemen transportasi publik di dalam operasional terminal akan dapat menentukan tingkat pemenuhan fungsi terminal. Penelitian ini bertujuan untuk membahas dan menganalisis tentang manajemen transportasi publik dalam rangka operasional terminal, khususnya di Terminal Mojosari Kabupaten Mojokerto yang tergolong masih baru dan dikelola secara langsung oleh Dinas Perhubungan Komunikasi Informatika (Dishubkominfo) Kabupaten Mojokerto. Â  Kata Kunci: Manajemen Transportasi Publik, Operasional Terminal.